Non-unit protection scheme for flexible DC transmission lines based on fitting the rate of change of line-mode voltage reverse traveling waves - Qixuan Zhang; Haifeng Li; Hainan Liu; Zhijie Wang (International Journal of Electrical Power & Energy Systems)
The existing non-unit traveling wave (TW) protection schemes of flexible direct current (DC) transmission lines based on time domain analysis cannot withstand high transition resistance. Thus, this study analyzes the TW propagation characteristics of flexible DC lines and obtains the characteristic differences in line-mode voltage reverse TW derivatives in the case of internal and external faults. The Levenberg–Marquardt method is used to fit the fault TW; the differences in the waveform features of the reverse TW rate-of-change under internal and external faults are extracted, and the characteristic quantities for internal and external fault identification are constructed by using fitting residuals and dominant term exponents in the fitting results. Finally, a simulation model for flexible DC transmission systems is established via PSCAD, and the effectiveness of the proposed scheme is verified. The results show that this method uses overall waveform characteristics to realize fault detection, is less affected by transition resistance, can withstand up to 800 Ω in transition resistance. Moreover, the influence of TW refraction and reflection on the fitting results is mitigated by means of fitting residuals, allowing for the reliable identification of faults across the entire line.